Ethylene Oxide: Cancer Evidence Integration and Dose–Response Implications. Issue 4 (10th December 2019) - Vincent, Melissa J.; Kozal, Jordan S.; Thompson, William J.; Maier, Andrew; Dotson, G. Scott; Best, Elizabeth A.; Mundt, Kenneth A.
The International Agency for Research on Cancer (IARC) and the United States Environmental Protection Agency (USEPA) classified ethylene oxide (EtO) as a known human carcinogen. Critically, both noted that the epidemiological evidence based on lymphoid and breast cancers was "limited, " but that the evidence in animal studies was "sufficient" and "extensive" (respectively) and that EtO is genotoxic. The USEPA derived one of the highest published inhalation unit risk (IUR) values (3 × 10 −3 per [µg/m 3 EtO]), based on results from 2 epidemiological studies. We performed focused reviews of the epidemiological and toxicological evidence on the carcinogenicity of EtO and considered the USEPA's reliance on a genotoxic mode of action to establish EtO's carcinogenicity and to determine likely dose–response patterns. Higher quality epidemiological studies demonstrated no increased risk of breast cancers or lymphohematopoietic malignancies (LHM). Similarly, toxicological studies and studies of early effect biomarkers in animals and humans provided no strong indication that EtO causes LHM or mammary cancers. Ultimately, animal data are inadequate to define the actual dose–response shape or predict tumor response at very low doses with any confidence. We conclude that the IARC and USEPA classification of EtO as a known human carcinogen overstates the underlying evidence and that the IUR derived by USEPA grossly overestimates risk.